Expedient synthesis of 9, 10-phenanthrenes via LiOPiv-promoted and palladium-catalysed aryne annulation by vinyl triflates. Issue 13 (22nd May 2018) - Hu, Jun-Tao; Zheng, Bin; Chen, Ying-Chun; Xiao, Qing
Abstract : An expedient synthesis of 9, 10-phenanthrenes via LiOPiv-promoted and palladium-catalysed aryne annulation by vinyl triflates. Abstract : A novel LiOPiv-promoted and palladium-catalysed formal [2 + 2 + 2] annulation reaction of vinyl triflates and o -silylaryl triflates via aryne intermediates has been developed. This methodology affords good to excellent yields of 9, 10-substituted phenanthrenes (including cyclohexa[ l ]phenanthrenes) and is tolerant of a variety of functional groups such as ester, cyano, and ketone.